Online instruction. A system for educational inclusion in the university setting - Vilaverde, Elena (Culture Education, 2020)
The goal of this article is to analyse online instruction's potential to foster the development of inclusive educational systems within higher education. To do so, it explores knowledge of virtual instruction environments and establishes three strands fostered by virtual learning systems which promote the inclusion of all higher education students. These three strands are made up of: (1) pedagogical models that enhance the learning process, such as Just-in-Time Instruction, Peer Instruction and Flipped Teaching; (2) eliminating barriers thanks to the flexibility of materials, times and spaces; (3) the development of student autonomy, stressing the value of the teacher's work and the student's activity, as well as the technological resources existing within online instruction. As a model of the implementation of this study, the proposal of the virtual campus of the International University of La Rioja will be presented, a university whose instruction takes place entirely online.
La enseñanza en línea. Un sistema para la inclusión educativa en el entorno universitario
Este artículo tiene como objetivo analizar las posibilidades que ofrece la enseñanza en línea para favorecer el desarrollo de sistemas educativos inclusivos en el marco de la Educación Superior. Para ello se profundiza en el conocimiento de los entornos virtuales de enseñanza y se establecen tres ejes que, potenciados por los sistemas de aprendizaje virtual, favorecen la inclusión de la totalidad del alumnado en la Educación Superior. Estos tres ejes están constituidos por: (1) modelos pedagógicos favorecedores del proceso de aprendizaje como Just-In-Time Teaching, Peer Instruction y Flip Teaching; (2) la eliminación de las barreras gracias a la flexibilidad de materiales, horarios y espacios; (3) el desarrollo de la autonomía del alumnado, enfatizando el valor de la labor del docente y de la actividad del alumno, así como recursos tecnológicos existentes en el marco de la enseñanza en línea. Como modelo de la implementación de este sistema, se presenta la propuesta del campus virtual de la Universidad Internacional de La Rioja, una universidad cuya docencia es en su totalidad en línea.
Keywords: virtual environment; online instruction; inclusion; attention to diversity; higher education; entorno virtual; enseñanza online; inclusión; atención a la diversidad; educación superior; JCR; Scopus